Quantifying the transport of biologics across intestinal barrier models in real-time by fluorescent imaging - Weller, Arjen; Hansen, Morten B.; Marie, Rodolphe; Hundahl, Adam C.; Hempel, Casper; Kempen, Paul J.; Frandsen, Henrik L.; Parhamifar, Ladan; Larsen, Jannik B.; Andresen, Thomas L. (Frontiers in Bioengineering and Biotechnology, 2022)
Unsuccessful clinical translation of orally delivered biological drugs remains a challenge in pharmaceutical development and has been linked to insufficient mechanistic understanding of intestinal drug transport. Live cell imaging could provide such mechanistic insights by directly tracking drug transport across intestinal barriers at subcellular resolution, however traditional intestinal in vitro models are not compatible with the necessary live cell imaging modalities. Here, we employed a novel microfluidic platform to develop an in vitro intestinal epithelial barrier compatible with advanced widefield- and confocal microscopy. We established a quantitative, multiplexed and high-temporal resolution imaging assay for investigating the cellular uptake and cross-barrier transport of biologics while simultaneously monitoring barrier integrity. As a proof-of-principle, we employ the generic model to monitor the transport of co-administrated cell penetrating peptide (TAT) and insulin. We show that while TAT displayed a concentration dependent difference in its transport mechanism and efficiency, insulin displayed cellular internalization, but was restricted from transport across the barrier. This illustrates how such a sophisticated imaging based barrier model can facilitate mechanistic studies of drug transport across intestinal barriers and aid in vivo and clinical translation in drug development.